Government ideology and monetary policy in OECD countries - Dodge Cahan; Luisa Dörr; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2019)
We examine the extent to which government ideology has influenced monetary policy in OECD countries since the 1970s. In line with important changes in the global economy and differences across countries, regression results yield heterogeneous inferences depending on the time period and the exchange rate regime/central bank dependence of the countries in the sample. Over the 1972-2010 period, Taylor rule specifications do not suggest a relationship between government ideology and monetary policy as measured by the short-term nominal interest rate or the rate of monetary expansion minus GDP trend growth. Monetary policy was, however, associated with government ideology in the 1990s: short-term nominal interest rates were lower under leftwing than rightwing governments when central banks depended on the directives of the government and exchange rates were flexible. Very independent central banks, however, raised interest rates when leftwing governments were in office. We describe the historical evidence for several individual countries.
Keywords: D72; E52; E58; C23; 330; government ideology; monetary policy; partisan politics; panel data